2000
DOI: 10.1111/j.1600-0781.2000.160304.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased phototoxicity of hydrochlorothiazide by photodegradation

Abstract: The photodegradation products of hydrochlorothiazide produced by ultraviolet (UV) radiation were investigated for their phototoxicity utilizing the photohemolysis and Candida albicans tests. Hydrochlorothiazide was irradiated for 30, 60, 90 and 120 min with a 250 W xenon arc lamp using a WG295 cut‐off filter. Irradiation of hydrochlorothiazide resulted in the gradual decrease of all three absorption bands (225, 270 and 320 nm), the blue shift of the 225 nm band, and the appearance of a new band around 290 nm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Once excited to reactive states by UV or visible light, these compounds produce damage throughout mechanisms mediated by free radical or, directly, by oxygen (14). Thiazide and its derivates, such as hydrochlorothiazide, are able to induce photosensitization by both systems (15), and the retinal phototoxic damage induced by these compounds represents a well-recognized clinical condition (5)(6)(7)(8)(9)(10)(11)(12). Recently, Mauget-Fa et al have described four cases of incidental retinal phototoxicity in patients receiving photosensitizing drugs, after exposure to a light sources usually known to be harmless, such as camera flash, electric welding arc light and microscope light.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once excited to reactive states by UV or visible light, these compounds produce damage throughout mechanisms mediated by free radical or, directly, by oxygen (14). Thiazide and its derivates, such as hydrochlorothiazide, are able to induce photosensitization by both systems (15), and the retinal phototoxic damage induced by these compounds represents a well-recognized clinical condition (5)(6)(7)(8)(9)(10)(11)(12). Recently, Mauget-Fa et al have described four cases of incidental retinal phototoxicity in patients receiving photosensitizing drugs, after exposure to a light sources usually known to be harmless, such as camera flash, electric welding arc light and microscope light.…”
Section: Discussionmentioning
confidence: 99%
“…The photosensitivity reactions of hydrochlorothiazide were described shortly after their introduction for the treatment of hypertension as early as the end of the 1950s (5). Adverse reactions attributed to hydrochlorothiazide include cutaneous (lichenoid reaction, vasculitis, erythema multiforme, purpura) and ocular side effects (6). Both the anterior and the posterior segment of the eye may be affected (7).…”
Section: Introductionmentioning
confidence: 99%
“…Then both irradiated and nonirradiated plates were incubated at room temperature for 48 h and 29.67 Root the appearance of the clear zone around the plates was compared. If more than 3 mm of clear zone around the paper discs was found only in the UV-irradiated plate, it was regarded as a positive finding (Han et al, 2000).…”
Section: Candida Albicans Testmentioning
confidence: 99%
“…C represents the absorbance of the supernatant which underwent hypotonic shock to produce maximal hemolysis (100% hemolysis). The mean hemolysis values of 5% or more were regarded as significant photohemolysis (Han et al, 2000).…”
Section: Photohemolysis Testmentioning
confidence: 99%
“…This last source of uncertainty may be relevant in the case of tamoxifen, as already mentioned; however, substances that do not appear in the ranking of compounds of most concern may have their comparative impact substantially increased by the inclusion of their derivative impact. For example, some researchers have suggested that the phototransformation products of triclosan, diclofenac or hydrochlorothiazide have a higher toxicity potential than their parent compounds (Han et al, 2000;Schmitt-Jansen et al, 2007). Nevertheless, the inclusion of phototransformation product impact is possible, if the chemical structures are identified, by applying the method proposed by van Zelm et al (2010).…”
Section: Model Limitationsmentioning
confidence: 99%